1996
DOI: 10.1111/j.1348-0421.1996.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Generation Triggered by Pseudomonas Proteases Facilitates Invasion of the Systemic Circulation by Pseudomonas aeruginosa

Abstract: To elucidate the mechanism of bacterial exoprotease in promotion of the intravascular dissemination of Pseudomonas aeruginosa, we examined the possible involvement of bradykinin (whose generation is induced by pseudomonal proteases in septic foci) in the invasion by bacteria, and in access of bacterial toxins to systemic blood circulation. P. aeruginosa 621 (PA 621), which produces very little protease, was injected intraperitoneally into mice together with pseudomonal exoproteases (elastase/alkaline protease)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Several factors, including tissue damage and infection, activates the generation of BK in tissues and plasma, and this occurs in infections with both gram-negative and gram-positive pathogens (Khan et al, 1993;Sakata et al, 1996;Mattsson et al, 2001). The formation of B 1 agonist through degradation of B 2 agonists is likely to occur and has been demonstrated in models of inflammation (Raymond et al, 1995) and following long-term incubation of BK on pulmonary fibroblasts (Koyama et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors, including tissue damage and infection, activates the generation of BK in tissues and plasma, and this occurs in infections with both gram-negative and gram-positive pathogens (Khan et al, 1993;Sakata et al, 1996;Mattsson et al, 2001). The formation of B 1 agonist through degradation of B 2 agonists is likely to occur and has been demonstrated in models of inflammation (Raymond et al, 1995) and following long-term incubation of BK on pulmonary fibroblasts (Koyama et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens that are involved in serious lung diseases such as cystic fibrosis (CF) can promote the generation of BK (Khan et al, 1993;Mattsson et al, 2001), and furthermore kallikrein levels have been found to be increased in the saliva of these patients (Lieberman and Littenberg, 1969). BK is involved in the bacterial dissemination of pathogens in vivo (Sakata et al, 1996), and the use of kinin receptor antagonists may be beneficial in controlling infections (Ridings et al, 1995;Heitsch, 2000). Overall, these findings suggest an important role for kinins in the initiation and maintenance of inflammation in infection.…”
mentioning
confidence: 99%
“…The identification and characterization of the C. neoformans extracellular protein is important because proteinases, esterases, and lipases are associated with virulence in other pathogens (5,10,11,12,14,20,22). C. neoformans is usually considered to be nonproteolytic (21), but a few studies have focused interest on its proteolytic activity (2,16).…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of the extracellular matrix is a pathological feature often observed in septic foci in bacterial infections (43). This suggested to us that extracellular proteinases produced by pathogenic microbes may induce disintegration of the tissue via direct degradation of the extracellular matrix (47,48).…”
Section: Proteolytic Activation Of Prommp-8 By Various Bacterial Protmentioning
confidence: 99%